E-learning methodologies fundamentals, technologies and applications - Goyal, Mukta; Krishnamurthi, Rajalakshmi; Yadav, Divakar (The Insitution of Engineering and Technology, 2021)
This book covers state of the art topics including user modeling for e-learning systems and cloud, IOT, and mobile-based frameworks. It also considers security challenges and ethical conduct using Blockchain technology
5.9 Virtual facilitators and learning environment
Keywords: Computer-assisted instruction -- Design.; elektronické knihy; electronic books